Break-induced ATR and Ddb1-Cul4(Cdt)² ubiquitin ligase-dependent nucleotide synthesis promotes homologous recombination repair in fission yeast. - Moss, J; Tinline-Purvis, H; Walker, C; Folkes, L; Stratford, MR; Hayles, J; Hoe, K; Kim, D; Park, H; Kearsey, S; Fleck, O; Holmberg, C; et al. (2010)
Nucleotide synthesis is a universal response to DNA damage, but how this response facilitates DNA repair and cell survival is unclear. Here we establish a role for DNA damage-induced nucleotide synthesis in homologous recombination (HR) repair in fission yeast. Using a genetic screen, we found the Ddb1-Cul4(Cdt)² ubiquitin ligase complex and ribonucleotide reductase (RNR) to be required for HR repair of a DNA double-strand break (DSB). The Ddb1-Cul4(Cdt)² ubiquitin ligase complex is required for degradation of Spd1, an inhibitor of RNR in fission yeast. Accordingly, deleting spd1(+) suppressed the DNA damage sensitivity and the reduced HR efficiency associated with loss of ddb1(+) or cdt2(+). Furthermore, we demonstrate a role for nucleotide synthesis in postsynaptic gap filling of resected ssDNA ends during HR repair. Finally, we define a role for Rad3 (ATR) in nucleotide synthesis and HR through increasing Cdt2 nuclear levels in response to DNA damage. Our findings support a model in which break-induced Rad3 and Ddb1-Cul4(Cdt)² ubiquitin ligase-dependent Spd1 degradation and RNR activation promotes postsynaptic ssDNA gap filling during HR repair.